IgG4-related lymphadenopathy - a difficult diagnosis - Balan Louis Gaspar (BMC, 2020)
Abstract Background The IgG4-related disease (IgG4-RD) is a systemic immune-mediated non-neoplastic disease associated with IgG4 positive plasma cells and fibrosis that often presents as a mass lesion. Although the disease could affect virtually any anatomical site, there are strong predilections for certain organs. IgG4-related lymphadenopathy can exhibit a broad morphologic spectrum. We describe a patient with IgG4-related lymphadenopathy with overlapping histological features that proved to be a diagnostic red herring. Case presentation A 58-year-old gentleman with multiple co-morbidities presented with obstructive jaundice, elevated transaminases, and bilateral inguinal and left axillary lymphadenopathy. Imaging of the abdomen and pelvis showed circumferential soft tissue thickening resulting in luminal narrowing of common and proximal bile duct with upstream intrahepatic biliary radicle dilatation, multiple enlarged lymph nodes, and homogenous soft tissue lesions in the tail of the pancreas and bilateral renal cortical parenchyma with perinephric soft tissue extension. Left inguinal, and axillary lymph node excision biopsies were suggestive of IgG4-RD. Serum IgG4 levels performed subsequently, were markedly elevated. The patient was treated with prednisone which led to resolutions of his symptoms, reduction in the size of the lesions, and reversal of abnormal laboratory parameters. Conclusion The diagnosis of IgG4-RD in lymph node excision biopsy is a difficult call to make and needs a multidisciplinary team. An early diagnosis renders timely intervention and prevents the progression of the disease and its complications.